Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1158/0008-5472.can-05-0124
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatase and Tensin Homologue Deleted on Chromosome 10 (PTEN) Has Nuclear Localization Signal–Like Sequences for Nuclear Import Mediated by Major Vault Protein

Abstract: Although phosphatase and tensin homologue deleted on chromosome 10 (PTEN) localization in the nucleus and cytoplasm is established, the mechanism is unknown. PTEN is a tumor suppressor phosphatase that causes cell cycle arrest and/or apoptosis. Nuclear-cytoplasmic compartmentalization may be a novel mechanism in regulating these events. PTEN does not contain a traditional nuclear localization sequence (NLS); however, we identified putative NLS-like sequences, which we analyzed by site-directed mutagenesis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
127
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(142 citation statements)
references
References 34 publications
8
127
0
2
Order By: Relevance
“…45 Our findings suggest that LAT, like CD247 and ZAP70, [41][42][43][44] plays a role in neurogenesis and that perturbation of this pathway may lead to neurodevelopmental phenotypes. They also provide an interesting example of the non-random organization of the genome 61 as gene dosage modification of (at least) one and five of the 9 and 28 genes mapping within the 220 kb BP2-BP3 and 600 kb BP4-BP5 intervals can influence the PTEN-antagonized (phosphatase and tensin homolog) PI3K/AKT and Ras/MAPK pathways: LAT, TAOK2, that encodes a PTEN-binding MAP kinase kinase kinase essential for dendrite morphogenesis, 62,63 MVP, the product of which interacts with PTEN and regulates its intracellular localization, 59,64,65 MAPK3, KCTD13, 37 and CDIPT (MIM: 605893) encoding an enzyme of the phosphatidylinositol synthesis pathway. Consistent with this view, the genes differentially expressed in cell lines of 16p11.2 600 kb BP4-BP5 carriers were enriched not only in pathways relevant to neurodevelopmental defects and ciliopathy but also in genes involved in phosphoinositide signaling.…”
Section: Discussionmentioning
confidence: 99%
“…45 Our findings suggest that LAT, like CD247 and ZAP70, [41][42][43][44] plays a role in neurogenesis and that perturbation of this pathway may lead to neurodevelopmental phenotypes. They also provide an interesting example of the non-random organization of the genome 61 as gene dosage modification of (at least) one and five of the 9 and 28 genes mapping within the 220 kb BP2-BP3 and 600 kb BP4-BP5 intervals can influence the PTEN-antagonized (phosphatase and tensin homolog) PI3K/AKT and Ras/MAPK pathways: LAT, TAOK2, that encodes a PTEN-binding MAP kinase kinase kinase essential for dendrite morphogenesis, 62,63 MVP, the product of which interacts with PTEN and regulates its intracellular localization, 59,64,65 MAPK3, KCTD13, 37 and CDIPT (MIM: 605893) encoding an enzyme of the phosphatidylinositol synthesis pathway. Consistent with this view, the genes differentially expressed in cell lines of 16p11.2 600 kb BP4-BP5 carriers were enriched not only in pathways relevant to neurodevelopmental defects and ciliopathy but also in genes involved in phosphoinositide signaling.…”
Section: Discussionmentioning
confidence: 99%
“…MCF-7 breast cancer cells were cultured in high-glucose DMEM containing 10% fetal bovine serum (FBS), penicillin, and streptomycin. The MCF-7 Tet-Off cell line expressing wildtype PTEN (PTEN:WT) was generated and maintained as previously described (14). Vector expression was controlled with 2 Ag/mL tetracycline (Tet).…”
Section: Methodsmentioning
confidence: 99%
“…We have recently shown that PTEN has bipartite nuclear localization signal (NLS)-like sequences required for MVPmediated nuclear import of PTEN (14). MVP reportedly interacts with the C2 domain of PTEN through the EF hand-like motif in a Ca 2+ -dependent manner in HeLa cells (10).…”
Section: Introductionmentioning
confidence: 99%
“…While no direct function for MVP has been described, reports suggest nuclear translocation of target proteins such as PTEN [12], nuclear exclusion of chemotherapeutic drugs [13] and as a scaffold protein downstream of the EGFR [14]. The PTEN / MVP interaction has been previously observed in a yeast two hybrid system, and co-immunoprecipitations have been performed in human cancer cells [12].…”
Section: Discussionmentioning
confidence: 99%